2013
DOI: 10.21273/horttech.23.6.735
|View full text |Cite
|
Sign up to set email alerts
|

Sensors for Improved Efficiency of Irrigation in Greenhouse and Nursery Production

Abstract: The use of sensors can provide quantitative information to help guide and automate the decision-making process for irrigation. This article provides an overview of the most common sensors that can be used for this purpose. Such sensors include those that are commonly used for weather stations as well as sensors to monitor the water status of the soil or substrate, and sensors that can be used to monitor and troubleshoot irrigation systems. Although collecting data with sensors is relatively easy, data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 44 publications
3
58
0
6
Order By: Relevance
“…Irrigation schedules increased WUE over the traditional industry practice of applying 1.8 cm/d by applying the appropriate amount of water based on plant needs. Similar results have been reported in other studies (Beeson et al, 2004;Regan, 1999;van Iersel et al, 2013). Nambuthiri et al (2017) reported that the moderate moisture deficit created by on-demand irrigation systems improved WUE by reducing the water use and leachate volume without a negative effect on plant growth.…”
Section: Resultssupporting
confidence: 89%
“…Irrigation schedules increased WUE over the traditional industry practice of applying 1.8 cm/d by applying the appropriate amount of water based on plant needs. Similar results have been reported in other studies (Beeson et al, 2004;Regan, 1999;van Iersel et al, 2013). Nambuthiri et al (2017) reported that the moderate moisture deficit created by on-demand irrigation systems improved WUE by reducing the water use and leachate volume without a negative effect on plant growth.…”
Section: Resultssupporting
confidence: 89%
“…However, aside from implementing precision irrigation strategies for producing containerized crops, there are other benefits when using these systems in commercial applications. Automated sensor-based irrigation is not only used to restrict irrigation for controlling height [6] but also to improve water use [24], plant growth uniformity [27], biomass [28], flower number [29], plant stress symptoms, and disease pressure [30] and can increase profitability of commercial producers compared to visual inspection-or timer-based irrigation scheduling [31].…”
Section: Discussionmentioning
confidence: 99%
“…For these reasons, maintaining optimal water status for soilless substrates is critical for continued plant growth. A sensor-based system for scheduling irrigation is a logical choice, and consists of sensors linked to an automated irrigation system that periodically measure the substrate water status at a specified interval (Nemali and Van Iersel, 2006;Van Iersel et al, 2013;Lea-Cox et al, 2017;Kaptein et al, 2019). Since water use by the seedling, along with drainage and evaporation, causes a decrease in substrate water level over time, the sensors detect these changes in the substrate volumetric water content (VWC, m 3 •m -3 ) or soil water potential (Ψ, kPa), and relay that information to an irrigation controller (Fig.…”
Section: Scheduling Irrigation In Small-volume Containersmentioning
confidence: 99%
“…2). The irrigation controller is programmed to control (open) selected irrigation valves for irrigation when the water level decreases below a set point (Belayneh et al, 2013;Van Iersel et al, 2013;Bayer et al, 2015;Wheeler et al, 2017). The irrigation is then allowed to continue until the upper set point of the programme is reached, at which time the irrigation valves are closed ( Fig.…”
Section: Scheduling Irrigation In Small-volume Containersmentioning
confidence: 99%
See 1 more Smart Citation